Chemoprevention of gastric cancer by celecoxib in rats. Issue 2 (14th January 2004) - Hu, P J; Yu, J; Zeng, Z R; Leung, W K; Lin, H L; Tang, B D; Bai, A H C; Sung, J J Y
Abstract : Background: Overexpression of cyclooxygenase 2 (COX-2) is frequently detected in gastric cancer and is believed to play a crucial role in gastric carcinogenesis. Aim: We examined the chemopreventive effect of a COX-2 inhibitor in an animal model of stomach carcinogenesis. Methods: Eighty six male Wistar rats were divided into six different treatment groups: group A, water alone (n = 5); group B, N -methyl- N′ -nitro- N -nitrosoguanidine (MNNG 100 μg/ml) (n = 16); group C, indomethacin (3 mg/kg/day) (n = 16); group D, celecoxib (5 mg/kg/day) (n = 17); group E, celecoxib (10 mg/kg/day) (n = 16); and group F, celecoxib (20 mg/kg/day) (n = 16). Group B–F animals were treated with 10% sodium chloride (in the initial six weeks) and MNNG in drinking water to induce adenocarinoma in the stomach. All animals received treatment for 40 weeks, and were sacrificed after death or at 48 weeks. Gastric neoplasm was evaluated by histology. Results: The incidences of gastric cancer were 0% in group A, 75% in group B, 68.8% in group C, 70.6% in group D, 18.8% in group E, and 31.3% in group F (p = 0.002, ANOVA). Compared with MNNG controls, treatment with celecoxib 10 mg/kg/day also showed lower tumour multiplicity (0.19 (0.40) v 1.00 (0.73); p = 0.004) and lower mean tumour volume (2.4 v 2805 mm 3 ; p = 0.02). Although tumours had significantly higher COX-2 expression than their adjacent normal tissues (p<0.02), there was no significant difference in COX-2 levels among tumours in the different treatment groups. The lowest tumour prostaglandin E2 level was found in the indomethacin treated group, suggesting that the chemopreventive effect of celecoxib may be mediated by a COX independent pathway. Conclusion: While treatment with indomethacin had no significant effect on tumour development, treatment with celecoxib reduced gastric cancer incidence and growth in rats.